How does knowledge sharing affect employee engagement? - Sui, Hai Juan; Irene, Wei Kiong Ting; Kweh, Qian Long; Liu, Yao (University of Malaya, 2018)
Employee engagement has emerged as a hot topic among academics and scholars over the last decade since organisations worldwide have adopted that lingo. However, little is known about how knowledge sharing, one of the main resources for organisations to maintain their competitive advantages, would affect employee engagement. Therefore, the objective of this study is to assess the impact of knowledge sharing on employee engagement based on the social capital theory. Data was obtained via questionnaires distributed to 180 randomly selected academics of public and private universities in Malaysia. This study applies multiple regression models to examine how three dimensions of knowledge sharing, namely structural, relational and cognitive, affect employee engagement. The results show all three aspects of knowledge sharing significantly and positively affect employee engagement. Specifically, work environment, leadership, organisational policies, communication, training and career development, compensation and team and co-workers in the knowledge sharing context improve employee engagement. This study is among the first to examine how organisations can better utilise knowledge sharing to engage their employees at work, which in turn help the organisation attain and sustain competitive advantages. Therefore, the addresses of knowledge sharing and employee engagement in this study are important and deserve further enrichments by including other knowledge management practices in the models.